2016
DOI: 10.1002/ange.201509653
|View full text |Cite
|
Sign up to set email alerts
|

Combining Metabolic Engineering and Electrocatalysis: Application to the Production of Polyamides from Sugar

Abstract: Biorefineries aim to convert biomass into aspectrum of products ranging from biofuels to specialty chemicals.T o achieve economically sustainable conversion, it is crucial to streamline the catalytic and downstream processing steps.I n this work, ar oute that combines bio-and electrocatalysis to convert glucose into bio-based unsaturated nylon-6,6 is reported. An engineered strain of Saccharomyces cerevisiae was used as the initial biocatalyst for the conversion of glucose into muconic acid, with the highest r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 42 publications
2
65
0
Order By: Relevance
“…The group of Balskus combined a microorganism as a 'living' biocatalyst, which produces hydrogen gas, and a heterogeneous catalyst (Pt or Pd) for the reduction of electron-deficient C-C double bonds in minimal media at room temperature (15 examples, up to 92% yield, see also section 'Reaction engineering to facilitate combinations of catalytic steps') 32 . Recently, Suastegui et al 33 realized a one-pot, but sequential process for the production of 3-hexenedioic acid starting from glucose. They combined an engineered Saccharomyces cerevisiae whole-cell biocatalyst for the production of muconic acid (0.5 g l -1 ) with a subsequent electrochemical reduction at ambient temperature and pressure.…”
Section: Nature Catalysismentioning
confidence: 99%
“…The group of Balskus combined a microorganism as a 'living' biocatalyst, which produces hydrogen gas, and a heterogeneous catalyst (Pt or Pd) for the reduction of electron-deficient C-C double bonds in minimal media at room temperature (15 examples, up to 92% yield, see also section 'Reaction engineering to facilitate combinations of catalytic steps') 32 . Recently, Suastegui et al 33 realized a one-pot, but sequential process for the production of 3-hexenedioic acid starting from glucose. They combined an engineered Saccharomyces cerevisiae whole-cell biocatalyst for the production of muconic acid (0.5 g l -1 ) with a subsequent electrochemical reduction at ambient temperature and pressure.…”
Section: Nature Catalysismentioning
confidence: 99%
“…In our study, we demonstrated how biosensors could be used in laboratory strains with limited engineering to improve titers, which at their best still were far from being commercially relevant. Indeed, in diploid yeast, production of 559.3 mg/L CCM has been recently reported 24 , whereas an E. coli-E. coli co-cultivation study has reported the production of 2 g/L CCM 47 . Though tolerance to low-pH fermentations should make yeast an economically feasible chassis for bio-based production of dicarboxylic acids such as CCM, the CCM biosensor design based on BenM may need to be adjusted or evolved as production hosts become better and the product titers become higher.…”
Section: Discussionmentioning
confidence: 99%
“…CCM is an intermediate from aromatic compound catabolism and an important precursor for bioplastics. Moreover, CCM biosynthesis recently has been refactored in yeast, yet without any high-throughput screening option available 24,25 . Third, BenM has a well-characterized DNA-binding site (here termed BenO) and mode of action ( Fig.…”
Section: A Prokaryote Transcription Activator In Yeastmentioning
confidence: 99%
See 1 more Smart Citation
“…15 A base solution containing ccMA and AA (internal standard) was prepared in D2O; separate solutions of HClO4, NaOH, and NaClO4 were prepared in D2O. Aliquots of each solution were added to J.…”
Section: Methodsmentioning
confidence: 99%